PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN SEJARAH ANGKATAN 2014 FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Robiana '; Marwoto Saiman; Tugiman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to: 1) To determine the correlation of the original school students with student motivation to learn Education Program History Armed 2014. 2) To determine the correlation of the original school students with student learning outcomes Education Program History Armed 2014. 3) To determine the correlation the entrance to the student motivation to learn students of History Education Armed 2014. 4) to determine the correlation track in student motivation to learn students of History Education Armed 2014. 5) to determine the correlation of motivation to learn the results of the students' education program history Force 2014 the Faculty of Education, University of Riau. The urgency of the motivation is the driving force, motive, and as a director of the goal. Board of Education, as a means of gathering agents of social change and the device must have the principle of unity or cooperation between institutions and members as well as people interested in it, without good cooperation, all the ideals for which the establishment educational institutions like the smoke that looks thick but easy to pass sendirinya.Populasi in this study were students of Education Studies Program History Force 2014 the Faculty of Education University of the 68 people. From the results of data processing using techniques Product Moment Correlation can be concluded that the motivation to learn has a significant impact on student learning outcomes. The effect of 55%, the remaining 45% are influenced by other factors not examined in this study, and it can be said that the students' motivation to learn the history of education courses University is in the medium category.Keywords: motivation, learning outcomes2